Voice-activated virtual space navigation - De La Cruz, Jean Roxanne A.; Joven, Margarette E.; Mayuga, Estela Sharon B.; Pinano, Ariane H. (2000)
Much attention has been placed recently on speech recognition systems due to the great advancement it will contribute to our technology. Speech recognition systems will provide the users with an easier and faster way of communicating with the computer than a keyboard or any other input device that our technology now has. This paper presents the implementation of speech recognition using pattern recognition approach. For the front-end processor, linear predictive coding (LPC) and vector quantization using binary split training algorithms were used. LPC produces the parametric representation of the speech signal. The binary split algorithm together with vector quantization clusters the vectors in the training set into eight 16-vector codebooks, one for each word in the vocabulary. The codebook contains 16 distinct vectors representing various pronunciations of the word. A reference pattern is identified for every codebook. For the recognizer part, the unknown speech signal is represented spectrally using LPC. Next, it is vector quantized to determine which reference pattern best represents the unknown speech signal. Speech recognition is applied to voice-activated navigation of a 3-5 solar system created with Open Graphics Library (OpenGL).
Thesis (B.S. Computer Science)--University of the Philippines Diliman.
Keywords: Automatic speech recognition; Pattern recognition systems; OpenGL; Linear predictive coding (LPC).; Open Graphics Library .